2022
DOI: 10.1111/obr.13453
|View full text |Cite
|
Sign up to set email alerts
|

Recent insights into vitamin D, adipocyte, and adipose tissue biology

Abstract: Summary Several studies bring strong evidence for an active role of vitamin D and its metabolites in physiological adipocyte and adipose tissue processes in adulthood. This role includes effects of vitamin D on key adipose tissue and adipocyte biology parameters, including adipogenesis, energy metabolism, and inflammation. Interestingly, recent data also point to a role of maternal vitamin D deficiency in adipocyte and adipose tissue metabolic programming in offspring. This review summarizes the current state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 153 publications
1
18
0
1
Order By: Relevance
“…Nevertheless, under high fat diet, we observed a rise in adiposity and insulin resistance in males, but not in females. Such Cells 2022, 11, 2024 2 of 14 observation strongly, together with others [12][13][14][15], supports an impact of VDD on adipose tissue physiology in perinatal context [16].…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Nevertheless, under high fat diet, we observed a rise in adiposity and insulin resistance in males, but not in females. Such Cells 2022, 11, 2024 2 of 14 observation strongly, together with others [12][13][14][15], supports an impact of VDD on adipose tissue physiology in perinatal context [16].…”
Section: Introductionsupporting
confidence: 54%
“…Of note, the relationship between vitamin D and adipose tissue physiology has been already demonstrated in adulthood, where VD anti-inflammatory effects in adipocyte and adipose tissue have been demonstrated in the context of obesity [16,17]. Indeed, obesity is classically associated with a low-grade inflammatory status in adipose tissue, resulting notably from the activation of several inflammatory signaling pathways including NF-B and p38/mapk [18].…”
Section: Introductionmentioning
confidence: 99%
“…These data support a longitudinal study that demonstrated 25(OH)D deficiency among patients who exhibited weight regain five-years post-RYGB, confirming that similar results are seen across these two different surgery types [ 11 ]. A possible mechanism of action for the impact of 25(OH)D on weight regain is the potential involvement of 25(OH)D in the suppression of genes involved in preadipocyte differentiation [ 24 , 42 , 43 ]. Higher 25(OH)D stores could therefore reduce the rate of adipogenesis and hence prevent weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism of VD uptake and release in adipose tissue is still unclear, but evidence demonstrates that many mechanisms, including the megalin/cubilin pathway, cholesterol (TC) transporters, and other mechanisms, are involved in 25(OH)D uptake. In addition, lipolysis may be involved in VD release, and this process is reported to be blunted in obese individuals, suggesting that the adipose is a pool of VD and that the release of poor VD from adipose tissue may cause lower serum VD levels in obese people [ 35 ]. This suggests that obesity is a contributing factor to VD deficiency independent of insufficient VD intake and lack of sunshine.…”
Section: The Relationship Of Vd Deficiency During Pregnancy and Obesi...mentioning
confidence: 99%
“…Apart from classical target organ cells, such as the intestine, parathyroid gland, and bone, VDR is also widely present in tissues, such as the heart, skin, brain, pancreas, and immune system, and moderates certain biologic effects, including glucose and lipid metabolism, cell proliferation and differentiation, and the activation of immune cells. In obese individuals, VDR expression is elevated in adipose tissue compared with lean individuals [ 35 ]. Additionally, uncoupling protein-1 (UCP-1) is a member of the uncoupling protein family involved in thermogenesis, energy metabolism, and obesity.…”
Section: The Relationship Of Vd Deficiency During Pregnancy and Obesi...mentioning
confidence: 99%